The Sensitivity of Quarterly Models of Wage Determination to Aggregation Assumptions - Rowley, J. C. R.; Wilton, D. A. (Quarterly Journal of Economics, 1974)
Journal Article The Sensitivity of Quarterly Models of Wage Determination to Aggregation Assumptions Get access J. C. R. Rowley, J. C. R. Rowley Economic Council of Canada and Statistics Canada Search for other works by this author on: Oxford Academic Google Scholar D. A. Wilton D. A. Wilton Economic Council of Canada and Statistics Canada Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 88, Issue 4, November 1974, Pages 671–680, https://doi.org/10.2307/1881829 Published: 01 November 1974